Sulfur isotope composition of individual compounds in immature organic-rich rocks and possible geochemical implications. (1st April 2020) - Shawar, Lubna; Said-Ahmad, Ward; Ellis, Geoffrey S.; Amrani, Alon
Abstract: We applied compound-specific sulfur isotope analysis (CSSIA) to organic matter (OM) extracted from ancient and immature organic-rich rocks from the Cretaceous Ghareb (Shefela Basin locality, Israel) and Miocene Monterey (Naples Beach locality, California, USA) Formations. Large variations in the δ 34 S values of different organosulfur compounds (OSCs), that reach up to 28‰ and 36‰, were observed in the Ghareb and Monterey samples, respectively. Additionally, some common OSCs in both locations showed consistent 34 S trends relative to each other. The consistent enrichment in 34 S of C35 hopane thiophene relative to iC20 thiophene in the studied sections probably resulted from differences in the timing of OM sulfurization. Reactive organic precursors quickly consume the most 34 S-depleted reduced S, while less reactive species incorporate the heavier residual S at a later time. Despite the differences in the depositional environments, ages, and the initial δ 34 S values of the reduced S (represented by the δ 34 S of pyrite) between the Ghareb and the Monterey Formations, the sulfurization order of common organic compounds seems to be similar. All of the δ 34 S values of OSCs are 34 S enriched relative to that of the coexisting pyrite with the exception of the C25 highly branched isoprenoid (HBI) thiophene in several samples from the Monterey Formation. The existence of 34 S-depleted sulfurized HBI may point to OM sulfurization that occurred at or near the sediment-water interface during the deposition of the Monterey. Moreover, the δ 34 S of steroid sulfides shows an inverse trend with the pristane/phytane ratio, which may indicate that the sulfurization mechanism of these OSCs are affected by redox conditions. Further investigation of CSSI values in immature rocks from other basins may help constrain the OM sulfurization process, timescale, and depositional conditions and their possible use as paleoenvironmental proxies.